2015
DOI: 10.1016/j.apsusc.2015.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Optical and mechanical properties of nanocrystalline ZrC thin films grown by pulsed laser deposition

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…To better understand the effect, we performed a Lorentz-Drude analysis of the data. In the non-irradiated ZrC, similar to our previous work [14], we found a low frequency band centered around 250 cm −1 . Although its position is below our lowest measured frequency in this study, the existence of this band is well confirmed by our previous data.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…To better understand the effect, we performed a Lorentz-Drude analysis of the data. In the non-irradiated ZrC, similar to our previous work [14], we found a low frequency band centered around 250 cm −1 . Although its position is below our lowest measured frequency in this study, the existence of this band is well confirmed by our previous data.…”
Section: Resultssupporting
confidence: 91%
“…We also showed that PLD grown films, being very flat and smooth, with surface rms values of the order of 1 nm, could be investigated with nanometer depth resolution by grazing incidence X-ray diffraction (GIXRD), X-ray reflectivity (XRR) and nanoindentation to observe the effect of irradiation on density, surface morphology, structure and mechanical properties. In this article we investigated the effect of Ar ions irradiation on the optical properties of the irradiated ZrC and ZrN films and compare the results to the previous reported ones [14].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several processing routes are available for producing ZrC: self-propagating synthesis (SHS) [14][15][16][17], mechanochemical synthesis [18][19][20], solution-based fabrication [21][22][23][24], and vapour routes such as chemical vapour deposition [25][26][27] and physical vapour deposition (PVD) [28][29][30]. For bulk production, the carbothermic reduction of zirconia is commonly used due to its low cost and reproducibility, similar to the Acheson [31] process for fabricating silicon carbide (SiC).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have a NaCl-type structure that is associated with ionic bonding. [1][2][3][4][5] By exploiting their favorable physical and chemical properties, on the one hand, the transition metal carbide refractory ceramics can be candidate materials for use in hightemperature nuclear applications. In particular, ZrC is being considered as a coating material for the tri-isotropic coated nuclear fuel used in high temperature reactors, replacing or in addition to the currently used SiC.…”
Section: Introductionmentioning
confidence: 99%